2016
DOI: 10.16910/jemr.9.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of emotion and perspective on remembering events: An eye-tracking study

Abstract: The main objective of this study is to investigate the effects of the emotional content of an event and participants’ perspective on the memory and eye-tracking measurements for central and peripheral de-tails. The data have been collected from 130 undergraduate male students (18- 33 ages). Three series of seven different emotional thematic photographs (positive, negative, neutral) were used. Participants were subjected to only one of the three series, either in his own perspective condition or observer perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…As a result, both Spanish and Chilean subjects were exposed to both domestic and foreign products at random. The exposure time was determined based on prior studies (Alonso-Dos-Santos et al , 2019; Gülçay and Cangöz, 2016). A prior pilot study confirmed that all the participants (10) were able to comprehend and process the stimuli in the time indicated.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, both Spanish and Chilean subjects were exposed to both domestic and foreign products at random. The exposure time was determined based on prior studies (Alonso-Dos-Santos et al , 2019; Gülçay and Cangöz, 2016). A prior pilot study confirmed that all the participants (10) were able to comprehend and process the stimuli in the time indicated.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment begins with calm phase, then a pre-calibration for each individual and then displays the three sport posters for ten seconds each one (total 300 s), a time recommended in previous research under similar conditions and validated in a pre-test (Alonso Dos Santos et al , 2019). A black image is displayed between each poster for two seconds (Gülçay and Cangöz, 2016). The subjects are shown three posters of the three sporting disciplines alternately for each group with the aim of eliminating the presentation effect: Three groups make up the same experimental factor.…”
Section: Methodsmentioning
confidence: 99%
“…During the experiment itself, the posters interspersed with black images for two seconds were displayed for eight seconds. The exposure time is based on Gülçay and Cangöz (2016) and contrasted in the qualitative validation process described previously.…”
Section: Methodsmentioning
confidence: 99%